Projetar um Limite d'Água. Proposta para uma Fracção da Frente Ribeirinha de Viana do Castelo - Sérgio Silva Ribeiro (2020)
This dissertation focuses on the study of the restructuring of a fraction of the Frente Ribeirinha de Viana do Castelo, leading to the presentation of a project proposal for its requalification. The site under study is currently integrated in the Detail Plan of the Frente Ribeirinha e Campo de Agonia - Viana do Castelo, developed under the Pólis program. Given the characteristics of the site, in a first phase of this dissertation, it is intended to interpret and understand the dynamics of the water fronts over time, in order to understand the origins of the ports, as well as the most striking changes in the urban network that these have provided. After understanding the different changes that the water fronts have undergone, it was essential to understand the urbanization process of Viana do Castelo over time. The historical contextualization regarding this urbanization process of the city began in 1258, after the charter granted by D. Afonso III. In this part, the main events that influenced the urban network of the city were determined, with the intention of understanding the historical chronology and the reason for its layout. Following this study on the historicity of Viana do Castelo, it was important to include the main plans developed for the city, especially those covering the land under study, namely the urban arrangement of the western area of the city of Viana do Castelo de Fernando Távora and the Pólis program. In the third phase it is intended to make an analysis of different projects, which proved essential for the concession of the final proposal. The choice of these reference projects was made taking into account the similarities with the present area under study, and it was opted for the requalification of Expo'98, focusing on some characteristics of the Pavilion of Portugal. It was also extremely important to list some foreign references that provided the definition of the volumes, as well as the programmatic proposals for their definition. Finally, after absorbing all the dynamics of urban evolution and understanding the different strategies used for the restructuring of the different spaces, the design practice of the space under study began, concluding with a text justifying the architectural options taken in the procedure of this proposal.